2015
DOI: 10.1088/0957-4484/26/22/225302
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the tunable exchange bias-like effect in magnetostatically-coupled two dimensional hybrid (hard/soft) composites

Abstract: Hybrid 2D hard-soft composites have been fabricated by combining soft (Co73Si27) and hard (NdCo5) magnetic materials with in-plane and out-of-plane magnetic anisotropies, respectively. They have been microstructured in a square lattice of CoSi anti-dots with NdCo dots within the holes. The magnetic properties of the dots allow us to introduce a magnetostatic stray field that can be controlled in direction and sense by their last saturating magnetic field. The magnetostatic interactions between dot and anti-dot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Tunable exchange bias-like effects in magnetostatically-coupled 2D hybrid composites are studied earlier by A. Hierro-Rodriguez et al [37]. Also, Yu et al…”
Section: Spin-wave Propagationmentioning
confidence: 76%
See 1 more Smart Citation
“…Tunable exchange bias-like effects in magnetostatically-coupled 2D hybrid composites are studied earlier by A. Hierro-Rodriguez et al [37]. Also, Yu et al…”
Section: Spin-wave Propagationmentioning
confidence: 76%
“…In addition to the better tunability of magnonic band structure, a larger propagation velocity of SWs has been demonstrated due to the presence of direct exchange coupling between the two materials in a filled antidot lattice (ADL) [34]. Tunable exchange bias-like effects in magnetostatically-coupled 2D hybrid composites are studied earlier by Hierro-Rodriguez et al [35]. Also, Yu et al demonstrated that a grating coupler of periodically nano-structured magnets provokes multidirectional emission of short-wavelength SWs with enhanced amplitude compared with a bare microwave antenna [36].…”
Section: Introductionmentioning
confidence: 94%
“…The fabrication of the magnetic circuit, composed of a cobalt bridge overcrossing a cobalt microwire, has been made by electron beam lithography using a Raith Elphy Plus e-beam lithography system installed in a LEO EVO 60 Scanning Electron Microscope [8]. Cobalt structures have been grown with magnetron DC sputtering from pure Co targets at normal incidence [8].…”
Section: Methodsmentioning
confidence: 99%
“…Cobalt structures have been grown with magnetron DC sputtering from pure Co targets at normal incidence [8].…”
Section: Methodsmentioning
confidence: 99%
“…Dipolar interactions have, for example, recently been shown to play a critical role in certain multilayer systems, namely, in the long-range "exchange bias" in ferromagnetic-antiferromagnetic heterostructures separated by non-magnetic layers 19,20 . In addition, dipolar-induced exchange-biaslike effects have been extensively studied in pseudo-spin valve like structures, i.e., hard and soft ferromagnetic layers separated by a non-magnetic layer 21,22 . Similar effects have also been observed in hard/soft nanostructured systems 23 .…”
mentioning
confidence: 99%